Determination of Fatty Acid Profiles Including Conjugated Linoleic Acids in Various Dairy Products - Okur, Ö.D.; Guzel-Seydim, Z. (Asian Journal of Chemistry, 2011)
The objective of the study was to determine conjugated linoleic acid (CLA) contents of milk and dairy products. Fatty acid profiles including conjugated linoleic acids of various dairy products were investigated. The amounts of fatty acids were determined in yogurt, butter, kaymak and variety of cheeses such as kasar made from ewe's milk, tulum, fresh kasar, old kashar and white brined cheese samples. Short chain fatty acids such as butyric acid, capric acid and caproic acid were also determined with this method as well as long chain fatty acids such as palmitic acid, oleic acid, miristic acid, linoleic acid and conjugated linoleic acid. Total conjugated linoleic acid amounts of aged kasar cheese, butter and kaymak were found as 2.06, 0.94 and 0.24 mg/g fat, respectively. It was observed that the higher the linoleic acid in the sample the higher concentration of conjugated linoleic acid. It was concluded that aging is an essential factor to obtain higher amounts of conjugated linoleic acid.